An 8-year Analysis of Magnesium Status in Elite International Track & Field Athletes. (3rd July 2020) - Pollock, N.; Chakraverty, R.; Taylor, I.; Killer, S. C.
Abstract: Magnesium plays a critical role in athlete health and performance. It is involved in numerous physiological mechanisms that support energy production, immune function, pain modulation, muscle function and bone health. Athletes may be susceptible to magnesium deficiency due to an increased utilization during exercise. Objective: This study reports on the magnesium status of 192 Olympic and Paralympic athletes over the course of eight years. Methods: Athletes on the British Athletics world class performance plan undertook blood testing for Red Cell Magnesium status. Their history of tendon pain, muscle and bone injury, ethnicity, sporting event and gender were also recorded. 510 samples from 192 athletes were included in the study. Results: On at least one blood test during the study time, 22% of athletes were identified as clinically deficient (<1.19 mmol/L). The average red cell magnesium concentration was 1.34 nmol/L. Magnesium was significantly lower in female athletes and those with Black or Mixed-Race ethnicity and was higher in Throws athletes and Paralympians with Cerebral Palsy. Athletes with a history of achilles or patella tendon pain had significantly lower magnesium levels than average. Conclusions: This study highlights the importance of investigating magnesium within this population to identify deficiency and support athlete health. Several areas for future work are identified to explore the relationship between magnesium and gender, ethnicity and tendon pain and muscle injury in athletes. Furthermore, new guidelines for magnesium status within athletics populations are proposed.